Tumor necrosis factor-? inhibitors in therapy for psoriatic arthritis - Vladimir Vasilyevich Badokin; I A Troshkina; Yu L Korsakova (Современная ревматология)
The paper presents the data available in the literature on the efficacy and tolerability of basic tumor necrosis factor α inhibitors (TNF α) etanercept, adalimumab, infliximab in the treatment of psoriatic arthritis (PsA) and their effects on the major manifestations of this disease - cutaneous and articular syndromes. It generalizes the authors experience in treating PA with infliximab. The value of TNF α inhibitors in the complex therapy of PsA and indications for their use in this disease are analyzed